Molecular interactions in composite wheat starch-Mesona chinensis polysaccharide gels: Rheological, textural, microstructural and retrogradation properties. (June 2018) - Yuris, Anynda; Matia-Merino, Lara; Hardacre, Allan Keith; Hindmarsh, Jason; Goh, Kelvin Kim Tha
Abstract: Composite Mesona chinensis polysaccharide (MCP) and wheat starch gels were studied using solid-state NMR, whereby close proximity (5 Å) between MCP and glucan polymers was established, indicating that both polymers interacted at molecular level. Rheological and amylose leaching data showed that this interaction was primarily between MCP and amylose leached during gelatinisation. The elastic modulus ( G′ ) and hardness of gels containing high starch concentration (≥8% w/w) was decreased at low (<3% w/w) MCP level and subsequently increased by more than 35% at 5% w/w MCP. In contrast, when starch concentration was lowered (5% w/w), the viscoelasticity gradually increased in the presence of MCP. Microscopy, DSC and syneresis data showed that a heterogeneous gel network microstructure was formed when there was insufficient MCP and/or amylose, which reduced the final G′ and hardness of the gels, and accelerated their retrogradation. Graphical abstract: Image 1 Highlights: Mesona Chinensis Polysaccharide (MCP) and wheat starch interact at molecular level. Interaction occurred during gelatinisation and involved leached amylose and MCP. The starch/MCP ratio determined the hardness and G′ of starch-MCP gels. Greater retrogradation and a porous gel microstructure was observed at low MCP.